Accuracy of self-perceived cardiovascular disease risk and factors predicting risk underestimation in perimenopausal and postmenopausal women in Ismailia, Egypt - Mirella Youssef Tawfik; Hanan H. Soliman; Zeinab F. Abdel-Fatah (SpringerOpen, 2024)
Abstract Background Cardiovascular disease (CVD) is the leading cause of death globally, with women at higher risk after menopause. This increased risk is attributed to both aging and hormonal changes. Prior research has established a link between CVD risk perception and adopting healthy behaviors to prevent CVD. This study aimed to assess the accuracy of self-perceived CVD risk in perimenopausal and postmenopausal women, and to identify factors that predict CVD risk underestimation among them. Methods A cross-sectional study was conducted in the administrative sectors of Suez Canal University campus in Ismailia, Egypt, over a period of eight months starting in July 2022. A total of 390 eligible women (employees and workers) were randomly selected. Participants were interviewed to obtain data on demographics, medical history, self-perceived risk of CVD, self-perceived general health, awareness of factors that increase the risk of developing CVD, perceived stress, health literacy, numeracy, and self-perceived 10-year risk of developing major cardiovascular events. They also underwent measurements of blood pressure, weight, and height. The updated 2019 WHO/CVD risk non-laboratory-based prediction chart for the North Africa and Middle East Region was used to predict the 10-year risk of major cardiovascular events for the study participants. Risk accuracy was measured by comparing self-perceived CVD risk with predicted CVD risk. Results The ratio of self-perceived to predicted moderate/high CVD risk was 27.7% to 44.3%, respectively. The accuracy of CVD risk perception was 68.2%. Kappa analysis results showed fair and significant agreement between self-perceived and predicted CVD risk (kappa ± SE = 35.9 ± 4.1%, p < 0 .001). The proportion of women who underestimated their risks was 24.1%. Of those in the high-risk group, 93.3% underestimated their CVD risk, compared to 50.6% in the moderate-risk group. Factors that significantly predicted CVD risk underestimation included being married (aOR 14.5; 95% CI 1.4-149.9), low income (aOR 2.321; 95% CI 1.09-4.909), high BMI (aOR 4.78; 95% CI 1.9-11.9), hypertension (aOR 3.5; 95% CI 2-6.2), and old age (aOR 1.46; 95% CI 1.3-1.6). Conclusions Approximately one-third of our study participants misperceived their CVD risk; of those who did, 75.8% underestimated it. Marital status, old age, low income, high BMI, and hypertension strongly predicted CVD risk underestimation. These findings identified the menopausal women subgroups that could benefit from targeted health interventions designed to reduce CVD risk underestimation and improve risk accuracy.